Systematics of the Southeast Asian mongooses (Herpestidae, Carnivora): solving the mystery of the elusive collared mongoose and Palawan mongoose. (1st December 2014) - Veron, Géraldine; Patou, Marie‐Lilith; Debruyne, Regis; Couloux, Arnaud; Fernandez, Desamarie Antonette P.; Wong, Siew Te; Fuchs, Jérome; Jennings, Andrew P.
<x xml:space="preserve">Abstract</x> Although recent molecular studies have clarified the phylogeny of mongooses, the systematics of the Southeast Asian species was incomplete as the collared mongoose Urva semitorquata and some debatable taxa (Hose's mongoose, Palawan mongoose) were missing in the analyses. We sequenced three mitochondrial (cytochrome b, ND2, control region) and one nuclear (beta‐fibrinogen intron 7) fragments of the Southeast Asian mongooses to clarify the systematic position of the different species and populations occurring in this region. Our results showed that the collared mongoose is closely related to the crab‐eating mongoose Urva urva, these two species forming a sister‐group to the short‐tailed mongoose Urva brachyura. Despite Sumatran collared mongooses having a peculiar orange phenotype, we showed that they exhibited very little genetic divergence to individuals from Borneo. In contrast, the populations of the short‐tailed mongoose from Borneo were strongly divergent to those from Peninsular Malaysia and Sumatra, and these might represent separate species. Within the crab‐eating mongoose, we observed little geographical genetic structure. Our study suggests that Hose's mongoose is not a valid species. The Palawan mongooses did not cluster with the other populations of the short‐tailed mongoose; they were closer to the collared mongoose and should be included in this species. © 2014 The Linnean Society of London